Nuclear export of the APC tumour suppressor controls β-catenin function in transcription - Rosin-Arbesfeld, Rina (Oxford University Press, 2003)
The adenomatous polyposis coli (APC) protein is inactivated in most colorectal tumours. APC loss is an early event in tumorigenesis, and causes an increase of nuclear β-catenin and its transcriptional activity. This is thought to be the driving force for tumour progression. APC shuttles in and out of the nucleus, but the functional significance of this has been controversial. Here, we show that APC truncations are nuclear in colorectal cancer cells and adenocarcinomas, and this correlates with loss of centrally located nuclear export signals. These signals confer efficient nuclear export as measured directly by fluorescence loss in photobleaching (FLIP), and they are critical for the function of APC in reducing the transcriptional activity of β-catenin in complementation assays of APC mutant colorectal cancer cells. Importantly, targeting a functional APC construct to the nucleus causes a striking nuclear accumulation of β-catenin without changing its transcriptional activity. Our evidence indicates that the rate of nuclear export of APC, rather than its nuclear import or steady-state levels, determines the transcriptional activity of β-catenin.